Prefrontal Cortex Activation During Dual Task With Increasing Cognitive Load in Subacute Stroke Patients: A Pilot Study - Hermand, Eric; Tapie, Bertrand; Dupuy, Olivier; Fraser, Sarah; Compagnat, Maxence; Salle, Jean Yves; Daviet, Jean Christophe; Perrochon, Anaick (Frontiers in Aging Neuroscience, 2019)
Stroke patients often exhibit difficulties performing a cognitive task while walking, defined as a dual task (DT). Their prefrontal cortex (PFC) activity is higher in DT than in single task (ST). The effects of an increasing load on PFC activity during DT in subacute stroke patients remains unexplored. Our objective was to assess the effects of N-back tasks (low/high load) on cerebral activity, gait parameters and cognitive performances. Eleven subacute stroke patients (days post-stroke 45.8±31.6) participated in this study (71.4±10 yrs, BMI 26.7±4.8 kg.m-2, Barthel index 81.8±11.0). Patients completed a STwalk, and 4 conditions with 1-back (low load) and 2-back (high load): STlow, SThigh, DTlow and DThigh. Overground walking was performed at a comfortable pace and -N-back conditions were carried out verbally. Both gait (speed, stride variability) and cognitive (rate of correct answers) performances were recorded. Changes in PFC oxyhemoglobin (∆O2Hb) and deoxyhemoglobin (∆HHb) were measured by functional near infrared spectroscopy (fNIRS). Results showed an increase of ∆O2Hb while walking, which was not augmented by cognitive loads in DT. Walking speed was reduced by low and high cognitive loads in DT compared to STwalk (P<0.05), but was not different between DTlow and DThigh. Cognitive performances were negatively impacted by both walking (P<0.05) and cognitive load (between ‘low’ and ‘high’, P<0.001). These data highlight a “ceiling” effect in ∆O2Hb levels while walking, leaving no available resources for simultaneous cognitive tasks, during the early recovery period following stroke. In these patients, cognitive, but not motor, performances declined with a higher cognitive load.